Towards a phenomenology of poverty: Defining poverty through the lived experiences of the 'poor'. (September 2020) - Simpson Reeves, Laura; Parsell, Cameron; Liu, Shuang
This article argues for the importance of defining poverty from the perspective of those who experience poverty. How poverty is defined and operationalised is critical to policy and academic debates, as this is intertwined with explanations, causes, and possible solutions. Yet current definitions are typically provided by the 'non-poor'. What we lack is knowledge of whether these definitions of the concept are similar to or different from those understood and conceptualised by those experiencing poverty. Australian poverty research has typically relied on panel data, administrative data, or surveys to construct and define 'poverty'. We propose that Australian poverty scholars embrace phenomenology as a way to highlight the voices of those experiencing poverty.